PENGEMBANGAN MEDIA KOMIK CERITA ANAK UNTUK MENINGKATKAN KETERAMPILAN MENULIS NARASI SISWA KELAS IV SDN WANAJAYA 05 KABUPATEN BEKASI - Nur Alina, Mutia; Ira Restu Kurnia (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
The low narrative writing skills of grade IV students can be influenced by the lack of innovation in the use of learning media in the classroom. There is a need for interesting learning media so that students can be more interested in writing narratives. This research aims to develop learning media such as children's story comic media to improve narrative writing skills in grade IV students in elementary schools. This research uses the Research and Development (R&D) method with the ADDIE model which consists of five stages, namely Analysis, Design, Development, Implementation, and Evaluation. For the validity test, three experts were assessed, namely material experts with a percentage of 100%, linguists with a percentage of 74.00%, and media experts with a percentage of 100%. In addition to the acquisition of three experts, to determine the feasibility also used assessments from the responses of educators and students, as for the responses of educators produced a percentage of 94.50%, and those produced by student responses produced 94.30%. So it can be said that children's story comic media can be declared very valid and very suitable to be used for learning in the classroom. As for testing the effectiveness, the assessment was taken from the Pretest and Post-test. The pre-test produced a percentage of 40.00% and the Post-test obtained a percentage result of 82.00%. So it can be said that children's story comic media is very effective to be used for learning in the classroom.